SiMGeBU Circuit Play for Early Childhood Earthquake Preparedness: Effects on Mitigation Skills, Gross Motor Development, and Cognitive Development - Aryani, Nini; Swandra Rahayu; Wilyanita, Nopa; Noorseha; Gadiza Raden (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Disaster preparedness in early childhood has received increasing global attention, yet empirical evidence remains limited on play-based interventions that simultaneously address disaster-specific skills and developmental outcomes. This study evaluates the SiMGeBU game, an Earthquake Mitigation Circuit designed to introduce earthquake preparedness through structured activity stations involving protective action, balance, route-following, and assembly-point practice. The study employed a quantitative quasi-experimental design with a multi-group dosage structure involving 36 children aged 5 to 6 years from three ’Aisyiyah Bustanul Athfal kindergartens in Kampar Regency, Indonesia. Data on earthquake mitigation skills, gross motor development, and cognitive development were collected using structured observation instruments and analyzed through MANOVA after normality, variance homogeneity, covariance homogeneity, and multicollinearity checks. The multivariate results showed a significant difference across intervention intensity groups for the combined outcomes, Pillai’s Trace = 0.412, F(8, 64) = 3.892, p = 0.001. Follow-up univariate analyses indicated significant effects on earthquake mitigation skills, F(2, 33) = 4.123, p = 0.025, η² = 0.200, and cognitive development, F(2, 33) = 4.567, p = 0.017, η² = 0.216. However, the effect on gross motor development was not statistically significant, p = 0.183. These findings suggest that circuit-based disaster preparedness play is more strongly associated with domain-specific mitigation skills and cognitive outcomes than with general motor development. By providing empirical evidence from an earthquake-prone Indonesian early childhood setting, this study contributes to global debates on child-centered disaster risk reduction, embodied preparedness education, and developmentally appropriate play-based interventions for young children. It also offers practical guidance for integrating preparedness routines into early childhood curricula without replacing motor education.